Letter to Jane Tolmach from Charles T. Manatt - Charles T. Manatt:::::: (1971)
In this January 8, 1971 letter, Charles T. Manatt congratulates Jane Tolmach on her appointment to the Democratic State Central Committee by Gary Hart, calling it a significant honor. He notes that he is a candidate for State Chairman and expresses interest in meeting with her to discuss strengthening the party's campaign organization. Manatt emphasizes that his campaign focuses on returning the party to effective "nuts and bolts" support for its nominees.